2018
DOI: 10.2216/17-2.1
|View full text |Cite
|
Sign up to set email alerts
|

The polyphasic analysis of two native Raphidiopsis isolates supports the unification of the genera Raphidiopsis and Cylindrospermopsis (Nostocales, Cyanobacteria)

Abstract: Raphidiopsis and Cylindrospermopsis are planktic, freshwater bloom-forming cyanobacteria of great concern to human health due to the production of potent cyanotoxins. The presence (in Cylindrospermopsis) or absence (in Raphidiopsis) of heterocytes is the traditional character used to distinguish them. This has led to misidentifications and to questions about the validity of the genus Raphidiopsis. We studied two strains of R. mediterranea isolated from Argentinean shallow lakes using a polyphasic approach that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(64 citation statements)
references
References 57 publications
1
56
0
2
Order By: Relevance
“…Filamentous cyanobacterial blooms are common in well‐mixed waters with different light intensity conditions (Aguilera et al., ; Havens, James, East, & Smith, ; Paerl et al., ). For instance, while some species such as Cylindrospermopsis raciborskii , a species phylogenetically related to R. mediterranea (Aguilera, Berrendero, Kaštovský, Echenique, & Salerno, in press; Moustaka‐Gouni, Kormas, Vardaka, Katsiapi, & Gkelis, ), succeed under high‐ Z eu / Z mix conditions (values ≥1) (Bonilla et al., ), P. agardhii blooms in highly turbid water columns ( Z eu / Z mix < 1; Bonilla et al., ) (Scheffer et al., ). Variable conditions in the Z eu / Z mix ratio during our study (range 0.37–1.42) may have favoured both cyanobacteria species in combination with changing nutrient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Filamentous cyanobacterial blooms are common in well‐mixed waters with different light intensity conditions (Aguilera et al., ; Havens, James, East, & Smith, ; Paerl et al., ). For instance, while some species such as Cylindrospermopsis raciborskii , a species phylogenetically related to R. mediterranea (Aguilera, Berrendero, Kaštovský, Echenique, & Salerno, in press; Moustaka‐Gouni, Kormas, Vardaka, Katsiapi, & Gkelis, ), succeed under high‐ Z eu / Z mix conditions (values ≥1) (Bonilla et al., ), P. agardhii blooms in highly turbid water columns ( Z eu / Z mix < 1; Bonilla et al., ) (Scheffer et al., ). Variable conditions in the Z eu / Z mix ratio during our study (range 0.37–1.42) may have favoured both cyanobacteria species in combination with changing nutrient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The bloom-forming freshwater filamentous cyanobacterium, Raphidiopsis raciborskii [previously named Cylindrospermopsis raciborskii (Aguilera et al, 2018)], is of increasing global environmental and social concerns because of its adverse effects on the quality of drinking water reservoirs and lakes as a result of the potential generation of toxic metabolites such as cylindrospermopsin (CYN) and saxitoxins (Hoff-Risseti et al, 2013;Lei et al, 2014;Botana, 2016;Martin et al, 2018). In recent decades, this diazotrophic cyanobacterium has spread from its native tropical region to subtropical and temperate zones (Burford et al, 2016;Burford et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Both collected and original sequences were manually aligned in Microsoft Word (Microsoft Corp., Redmond, WA, USA) according to the secondary structure of the 16S molecule ( Reh akov a et al 2014). The jModel-test2 software was used for estimation of the best fit substitution model, found to be GTR+I+G (Darriba et al 2012) for both Bayesian Inference (BI) and Maximum Likelihood (ML) as demonstrated previously , Mare s 2017, Aguilera et al 2018. For ML analysis we used RaxML v.7.2.8 (Stamatakis et al 2008) with 1,000 bootstrap replicates.…”
Section: Methodsmentioning
confidence: 99%